ECONOMIC AND ACCOUNTING CONCEPTS. - Bowers, Russell (The Accounting Review, 1945)
Abstract Economics is concerned with the economy of a major unit of society, one which extends beyond the limits of any individual firm. Business accounting, on the other hand, deals with the economy of subordinate parts of a larger unit of society. The unit used by the accountant is typically the productive business firm. Economy is meaningless unless de fined in relation to the point of view of somebody or some group taken as a collective unit. Recognition of three distinct "levels" or types of context for any discussion about economic problems are that the problem of the individual or natural person as a consumer. The business firm as a producer. It is with the firm, often in the form of a corporate enterprise operating as a trading unit within a money economy, that accounting is concerned. The last level is that of national, or, better, total economy. The economy of the business firm can be expressed adequately in accounting terms. The economy of the individual also may be expressed in similar terms if exception is made for that segment of an individual's economy which is not expressed in money, that is, the individual may economize in the exercise of alternative modes of use of his non-monetary resources, as when he performs a service for himself.